MANGROVES AS HOLOBIONTS AND OTHER SEA STORIES - Montes Gabriel, Diego; Becerril Jiménez, Mariana B.; Hernández Martínez, Enrique; Vázquez Rosas Landa, Mirna (Kuxulkab', 2024)
Mangroves are complex and very important ecosystems as they offer coastal protection, carbon sequestration and provide habitat for sharks, rays, crustaceans, fish and others, which is why they may represent true holobionts, entities formed by plants, animals and an interdependent microbial community that has co-evolved for millions of years. Microbes play crucial roles such as nitrogen fixation and nutrient solubilization for both plants and the entire ecosystem. Understanding mangroves as holobionts is essential to appreciate their complexity and make informed decisions about their conservation; this holistic perspective can be applied to other ecosystems promoting more effective environmental management and a better understanding of life.
Keywords: Mangrove; Holobiont; Microbiome; Conservation; Ecosystem